The Influence of Social Media on Input-Output Transformation in Digital Production Project Management - Juliana, Elisabeth; Linda, Rosa (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2025)
In today's digital era, social media has become a central driver of change in communication, collaboration, and technology-enabled project management. This study aims to investigate the impact of social media adoption on input–output transformation efficiency in digital production project management. Using a mixed-methods sequential explanatory design, multiple linear regression was conducted in the quantitative phase on 120 digital project professionals, followed by qualitative follow-up interviews with 10 key informants. The results show that the frequency of use, level of digital collaboration, and platform integration all have a significant positive impact on the effectiveness of converting resources into digital outputs, with an adjusted R² of 0.624. Qualitative findings also demonstrate that social media is a catalyst for information sharing, team coordination, and productivity. Theoretically, this study applies the Leontief Input–Output model to online settings, and practically, it offers strategic implications for project managers to streamline social media to improve resource and workflow efficiency. The novelty lies in empirically validating social media as a mediating variable within the Leontief Input–Output framework for digital production projects, offering a new socio-technical perspective on project efficiency.